Validity and reliability evidence of the Psychological Capital Questionnaire-12 in a sample of Mexican workers - Santana-Cárdenas, Soraya; Viseu, João Nuno; López-Núñez, María Inmaculada; Jesus, Saúl Neves (Anales de Psicología / Annals of Psychology, 2018)
Psychological capital is a construct that is included in the positive organizational behavior framework, which is based on positive psychology principles. This concept is composed by four dimensions, self-efficacy, hope, resilience, and optimism, which have a synergistic action. The aim of this study was to report the psychometric properties of one of the measures of psychological capital, the Psychological Capital Questionnaire-12 (PCQ-12), in a sample of 396 Mexican workers. This instruments’ factor structure was analyzed through a confirmatory factor analysis. Reliability was assessed with the Cronbach’s Alpha and Composite Reliability coefficients. Furthermore, convergent and discriminant validity were also evaluated. Based on three concurrent models, it was observed that the model which possessed a better fit was composed by four-correlated factors. The implications of these results are discussed, and recommendations are provided for future researches. This paper, which presents a different factor structure than the usual of psychological capital, suggests that cultural differences may play a crucial role on the way the assessed construct behaves.